2017
DOI: 10.1186/s12879-017-2335-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of delayed culture conversion among Ugandan patients

Abstract: BackgroundEstimates of month-2 culture conversion, a proxy indicator of tuberculosis (TB) treatment efficacy in phase-2 trials can vary by culture-type and geographically with lower rates reported among African sites. The sub-study aimed at comparing TB detection rates of different culture media, within and across rifampicin-based regimens (R10, 15 and 20 mg/Kg) over a 6-month treatment follow-up period, and to establish predictors of month-2 culture non-conversion among HIV-negative TB patients enrolled at RI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
1
8
2
Order By: Relevance
“…These were; registration group (new/previously treated), HIV co-infection (yes/no), BMI (<18.5/≥18.5), baseline sputum smear grade (<3+/≥3+) and radiological findings (cavitary lesions/ no cavitary lesions). This finding on significant predictors of late culture conversion was also supported by different studies conducted across the world [ 9 , 10 , 16 , 23 , 27 29 ].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…These were; registration group (new/previously treated), HIV co-infection (yes/no), BMI (<18.5/≥18.5), baseline sputum smear grade (<3+/≥3+) and radiological findings (cavitary lesions/ no cavitary lesions). This finding on significant predictors of late culture conversion was also supported by different studies conducted across the world [ 9 , 10 , 16 , 23 , 27 29 ].…”
Section: Discussionsupporting
confidence: 77%
“…This might be because of variation in the status of the setting and other patient characteristics. In fact, this extent of the outcome is lower than the finding of a study conducted in Uganda (55%) [ 23 ].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Baseline time to TB detection (TTD) was defined as time (in days) until MGIT culture showed a positive result at initial sputum culture [ 6 , 16 ]. Atwine et al reported a twofold increase in risk of culture conversion at 2 months in patients with baseline TTD < 14 days compared with ≥14 days [ 17 ]. This study was approved by the Ethics Committee of Jikei University School of Medicine [No.…”
Section: Methodsmentioning
confidence: 99%
“…Atwine et al reported a twofold increase in risk of culture conversion at 2 months in patients with baseline TTD <14 days compared with ≥14 days [17]. This study was approved by the Ethics Committee…”
Section: Methodsmentioning
confidence: 99%